You have come a long way baby: citizens at conception? Prenatal personhood and SCHIP eligibility - Hennessy, Judith; Cliath, Alison Grace (2004)
What are the (un)intended consequences of a citizens at conception policy? This article explores whether redefining a child does indeed spur a material expansion of benefits through the States Children's Insurance Program (SCHIP) or whether this action can be better understood as a struggle over symbolic boundaries of fetal personhood, social boundaries of citizenship, and the attendant challenges to women's reproductive rights. - Reproduced.
Keywords: Nationality